2023
DOI: 10.3389/fnins.2023.1096339
|View full text |Cite
|
Sign up to set email alerts
|

Manual acupuncture for neuromusculoskeletal disorders: The selection of stimulation parameters and corresponding effects

Abstract: As a minimally invasive method of physical stimulation, manual acupuncture (MA) is used globally as a sort of therapy for neuromusculoskeletal disorders. In addition to selecting appropriate acupoints, acupuncturists should also determine the stimulation parameters of needling, such as the manipulation (lifting-thrusting or twirling), needling amplitude, velocity, and stimulation time. At present, most studies focus on acupoint combination and mechanism of MA, the relationship between stimulation parameters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Then, the collected original RGB video signal dataset was segmented and cropped. In the actual data acquisition and communication with acupuncturists, we found that for a standard manipulation, the operation time of the twisting and lifting cycle was usually about 1 s [37]. Therefore, we chose 1 s as an MAM sequence cycle in constructing the dataset.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the collected original RGB video signal dataset was segmented and cropped. In the actual data acquisition and communication with acupuncturists, we found that for a standard manipulation, the operation time of the twisting and lifting cycle was usually about 1 s [37]. Therefore, we chose 1 s as an MAM sequence cycle in constructing the dataset.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Generally, in the attention mechanism-based methods [37], the query matrix Q is used to denote the information that the model is concerned with at the current moment, the key matrix K is used to denote the information that matches Q, and the value matrix V contains the actual information in the input sequence.…”
Section: Iammentioning
confidence: 99%